Emerging and re-emerging infectious diseases: tackling the challenge on a global level (Italian Journal of Public Health, 2011)
After the Second World War the general feeling was to have solved almost all the most important problems of dealing with infectious diseases. This feeling appeared to be appropriate and supported by the identification of new allies such as new antibiotics and vaccines. However, in 1991 the Institute of Medicine of the National Research Council in the US appointed a 19-member multidisciplinary expert committee to study the old and new microbial threats to health.